SAFEGUARDING CHILDHOOD: A PARADIGM OF EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) - Dr Tabassum Naz; Prof. Dr. Azhar Mehmood (International Journal of Contemporary Issues in Social Sciences, 2024)
Achieving sustainable development goals requires a comprehensive approach that includes providing education within a safe and nurturing environment and safeguarding childhood. This study focuses on the child protection procedures and policies for students in Federal Government schools located in Islamabad, covering both rural and urban areas. The primary objectives of the study were to explore teachers’ perceptions regarding child protection issues and their awareness of prevention programs in Educational Institutions of Islamabad Capital Territory (ICT), to identify the existing child protection mechanisms in these institutions, and to examine gender-based differences in teachers’ perceptions and training related to child protection mechanisms. The study adopted a descriptive research design. Data were collected using a five-point Likert scale questionnaire designed to measure various aspects of teachers’ perceptions and awareness. The study population included all teachers in public ICT schools, and a representative sample of 600 teachers was selected using stratified random sampling. The data was analyzed using SPSS version 20. Analysis shows there is high awareness and positive perceptions of child protection policies and procedures. Importantly, there were no significant differences between male and female teachers regarding child protection-related perceptions and training across all measures, suggesting a uniform approach to child protection training and awareness within the institutions surveyed. These findings have important implications for both policymakers and educators. It is recommended that educational institutions strengthen child protection training programs to ensure that all teachers receive consistent and comprehensive training. In addition, schools should regularly evaluate their child protection mechanisms to assess their effectiveness and identify areas for improvement. By maintaining high standards of child protection, educational institutions can contribute to wider sustainability goals by creating a safe learning environment that supports the well-being and development of all students. This research highlights the importance of a multifaceted approach to child protection in education settings, combining comprehensive training, consistent policy implementation and ongoing evaluation to safeguard children’s well-being and promote safe educational environments.